ASYNCHRONOUS COMPUTER MEDIATED COMMUNICATION: AN EXPLORATORY STUDY ON STUDENTS’ E-LEARNING EXPERIENCE AND THEIR INTERACTION - Ahmad, Dian Resty Pratiwi (Journal of Islam and Science, 2021)
Asynchronous CMC is an online learning that has time difference between the period of teaching using online apps and the messages. This study aimed to find out students’ interaction and activities on the asynchronous CMC through Google Classroom and Whatsapp Group. This study employed mixed method namely exploratory research design. There were 20 participants involved as the sample of this study. The qualitative data were collected and analysed in order to develop the quantitative instrument. Thus, this research used observation recordings and questionnaire which consisted of 12 main questions. This study found that at least there are four main activities on asynchronous learning namely communication, learning process, material and evaluation. The participants showed different responses in two activities namely communication and learning process in both applications namely Whatsapp and Google Classroom. Meanwhile, in material and evaluation the participants showed relatively similar percentage. Besides, this study found that traditional face-to-face learning is easier than online learning in terms of communication and learning materials. This study suggests that the details of this finding need to be investigated further.